Digital Literacy Management in Primary School: A Multi-Site Study at SDN Sungai Miai 7 and SDN Melayu 2 Banjarmasin - Resyadilla Azkia; Ahmad Suriansyah; Suhaimi Suhaimi (Journal of Educational Sciences, 2026)
The development of information technology requires the education sector to strengthen digital literacy as part of 21st-century competencies. However, its implementation in primary schools faces challenges in curriculum integration, teacher competence, and support. This study analyzes principal leadership in managing digital literacy at two primary schools in Banjarmasin using a multi-site design. Data were collected through interviews, observations, and documentation, and analyzed through single-site and cross-site analysis. The findings indicate that digital literacy management is enacted through three interconnected strategies; curriculum implementation, human resource development, and partnership. The results reveal patterns across sites. SDN Sungai Miai 7 employes a systematic and data-driven approach grounded in national education assessment reports and integrated into planning documents (RKJM and RKAS), supported by structured mentoring from senior teachers and a professional learning community. In contrast, SDN Melayu 2 adopts a flexible and contextual approach, characterized by adaptive curriculum practices, peer-based collaborative professional development, and partnerships oriented toward technical and infrastructural support. Despite these differences, both schools demonstrate that digital literacy management emerges from the synergy of these strategies, strengthened by stakeholder involvement and principal leadership. These findings highlight that digital literacy management is context-dependent, where both structured and adaptive approaches can effectively support implementation in primary education settings.